The state of food and agriculture 1982 - Food and Agriculture Organisation (Rome : Food and Agriculture Organisation, 1983)
This edition examines the state of natural resources and the human environment for food and agriculture. Problems and strategies in developing regions.
lje 14/06/17
Ref.
Keywords: Agricultural industries - Periodicals; Agricultural industries